Expanding knowledge frontiers in entrepreneurship: examining bricolage and effectuation. Issue 5 (14th June 2020) - Vasconcelos Scazziota, Vanessa; Andreassi, Tales; Ribeiro Serra, Fernando Antonio; Guerrazzi, Luiz
Abstract : Purpose: Our purpose is to evaluate effectuation and bricolage through their unique and shared references to understand possible overlaps and conceptual complementarities between these theoretical approaches. Design/methodology/approach: The use of bibliometric techniques to examining simultaneously both theoretical approaches is one of the distinctions of this work. Another important methodological feature is the use of co-citation and bibliographic coupling and their interaction, to verify 179 published documents relating to their references. Findings: The study reveals the intellectual structures underlying the approaches and differences originating from their knowledge bases, as well as the research trends. Originality/value: By identifying the differences in the decision process and behaviors that culminate in opportunity creation in each, it offers a complementary vision of previous works. The evidence stresses it is interesting to explore their integration, considering the complementarity of their unique aspects.